Literary heritage of Bazar zhyrau - Karibozuly, Б.; Oralova, Г.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The works of Bazar Ondasuly, which have a special place in Kazakh literary studies, are also a literary heritage of national literature. In this article, the national character of Bazar Zhyrau’s heritage and the artistic thinking level are determined, and the mutual connection of traditions and innovations in the glorification of Bazar Zhyrau is evaluated. Bazaar Zhyrau’s peculiar way of thinking, speech, and worldview is recognized. Based on the classification of the chants of Bazar Zhyrau, several of its internal types are distinguished. The connection of Bazar Zhyrau with the established literary tradition is substantiated and his place in Kazakh literature is analyzed. It is not only the task of science and culture, but also the moral duty of the older generation to make sure that the best people in our history are not forgotten by the younger generation. It is about the historical destiny, the interrelation of the literature of the Turkic-speaking peoples, the continuation of the centuries-old tradition. Our national literature was greatly influenced by the literature of the East and the West, as well as the world in general. The article focuses on the peculiarities of Bazar Zhyrau in epos writing and provides a theoretical analysis. The works of Bazar Ondasuly, which have a special place in Kazakh literary studies, are also an artistic heritage of national literature. The educational value and aesthetic value of the works propagated by humanistic ideas, moral qualities of the works written in the tradition of Eastern civilization and literature are differentiated.